Evaluation of Repairability of Different Resin Composites After ph and Thermal Cycling - Esma Balın; Baykal Yılmaz; Güll Dinç Ata (Ankara University, 2022)
Purpose: The aim of this study was to investigate the effect of different aging methods on repair bond strength of different types of composite resins. Materials and Methods: Thirty resin composite blocks (5mm×5mm×4mm) were built up with a nanohybrid universal resin composite and a bulk-fill resin composite according to the manufacturer's instructions, using a silicone matrix. Indirect resin composite blocks were obtained with similar dimensions from prefabricated blocks by microtome. All the samples were air abraded with 50µm aluminum oxide particles. Specimens were then repaired with a nanohybrid resin composite using two step adhesive system. All these specimens were then randomly divided into three groups for aging process (pH cycle, thermal cycle and control group) and tested for shear bond strength. Results were recorded in MPa. Additionally fractured specimens were examined under stereomicroscope to determine the mode of failure. The data was statistically analyzed using two-way ANOVA and Bonferroni correction test (p lt;0,05). Results: Statistically significant effect was found on the bond strength values of the aging method and the restorative material (p lt;0,05). Thermal cycle applied samples showed statistically significantly lower bond strength values than both pH cycle and control group samples (p lt;0,05). Regardless of the aging method, the overall bond strength of Tetric N-Ceram Bulk Fill is statistically significantly higher than bond strength of Tetric CAD (p lt;0,05). Conclusions: Thermal cycle application is an effective aging method and air abrasion has different effects on repair bond strength of the restorative materials according to the content of the materials.